Transformasi Kompetensi Guru Pai Di Abad 21: Perubahan Paradigma Pembelajaran Di Era Digital - Rahmadani Akbar; Nur Saidah (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study analyzes the challenges and opportunities in developing the competencies of Islamic religious education (PAI) teachers in the 21st century, focusing on using technology in learning. In the digital era, PAI teachers need to improve digital literacy and relevant pedagogical competencies. The research method used is library research with a descriptive-critical approach, collecting data from various academic sources regarding the competencies of PAI teachers in the 21st century. The results of this study indicate that the main challenges include limited digital literacy, teachers' reluctance to change traditional teaching methods, and minimal access to technology-based training. However, there are great opportunities for competency development through access to digital educational resources and online training programs. This study emphasizes the importance of digital literacy for teachers and their role as facilitators in creating an interactive and responsive learning environment to students' needs. By implementing an innovative approach to learning, it is hoped that the PAI teaching process will be more effective and relevant for students in the digital era. These findings provide recommendations for education policies to improve teacher training and technology integration in the PAI curriculum.